Malignant Prolactinoma With Liver Metastases Masquerading as Metastatic Gastrointestinal Stromal Tumor: A Case Report and Literature Review - Hong, A Ram; Yoon, Jee Hee; Kim, Hee Kyung; Kang, Ho-Cheol (Frontiers in Endocrinology, 2020)
Pituitary carcinomas are rare diseases defined as pituitary tumors with metastases. In this report, we describe a case of malignant prolactinoma with liver metastases masquerading as metastatic gastrointestinal stromal tumor (GIST). A 54–year–old woman received dopamine agonists for macroprolactinoma for 2 years, followed by transsphenoidal surgery due to a poor response to medical therapy. Despite the continuation of dopamine agonist after surgery, serum prolactin level progressively increased to above 8000 ng/ml in 5 years. There was no evidence of disease recurrence on sella magnetic resonance imaging (MRI). She stopped medical therapy. Meanwhile, she was diagnosed with GIST accompanied by liver and peritoneal metastases. After a 2–month treatment with imatinib, she suddenly presented with headache and visual impairment. Sella MRI showed a 3.3–cm sized pituitary mass, and serum prolactin levels were still high. For the recurred mass, she underwent a second surgery followed by radiation therapy. During the imatinib treatment for GIST, main mass and peritoneal metastases were dramatically decreased, but liver metastases were markedly aggravated. Liver masses were eventually confirmed as metastases from prolactin-producing pituitary carcinoma and not from GIST by percutaneous biopsy. Unfortunately, she died 6 months after the second surgery due to acute renal failure and sepsis. This case suggests that highly sustained serum prolactin levels during the dopamine agonist may indicate prolactin-producing pituitary carcinomas with hidden metastases.